The Church's Strategy and Jesus' Teaching Principle in Shaping Responsible Character - Meike Irmawati Tompira; Tonny Andrian Stefanus; Maria Titik Windarti (International Forum of Researchers and Lecturers, 2024)
This study aims to explore church strategies in shaping the character of responsible servants and identify the teaching principles of Jesus according to the Gospel of Matthew 5-7 to be adapted in Christian Religious Education. This article uses descriptive qualitative method based on literature review. The results show that effective church strategies involve discipleship, pastoral counselling, fellowship, and Bible-based teaching. In addition, Jesus' teaching principles such as love, prayer, and obedience become the foundation of responsible character building. This study recommends integrating church strategies and Jesus' teaching principles to support the character building of church ministers and PAK students.